1992
DOI: 10.1152/ajpcell.1992.263.6.c1152
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cultured chemoreceptor cells dissociated from adult rabbit carotid body

Abstract: Short-term cell cultures were obtained from enzymatically dissociated carotid bodies from adult rabbits, and morphological and functional characterization of the cultured chemoreceptor cells were carried out. Under phase contrast, freshly isolated type I cells are round, bright, and 10-14 microns in diameter and exhibit strong fluorescence when stained with the glyoxylic acid technique. The content of endogenous dopamine in the cultures increased from 80 pmol/10(5) cells 2 h after plating the cells to 200 pmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…After tracheostomy, the carotid artery bif urcations were removed, and the animals were killed by an intracardiac bolus injection of pentobarbital sodium. The CBs were cleaned of surrounding connective tissue and enzymatically dispersed as described elsewhere (Pérez-García et al, 1992;L ópez-L ópez et al, 1997). Dispersed cells were plated onto poly-L-lysine-coated coverslips placed in 6-well dishes with 1 ml of DM EM:F-12 (1:1) with 5% FBS and maintained in culture for up to 96 hr.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After tracheostomy, the carotid artery bif urcations were removed, and the animals were killed by an intracardiac bolus injection of pentobarbital sodium. The CBs were cleaned of surrounding connective tissue and enzymatically dispersed as described elsewhere (Pérez-García et al, 1992;L ópez-L ópez et al, 1997). Dispersed cells were plated onto poly-L-lysine-coated coverslips placed in 6-well dishes with 1 ml of DM EM:F-12 (1:1) with 5% FBS and maintained in culture for up to 96 hr.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the rabbit CB chemoreceptors, three different voltage-dependent K ϩ channels have been described in singlechannel studies (Ganfornina and López Barneo, 1992a), and a detailed electrophysiological characterization of these currents, particularly of the O 2 -sensitive K ϩ current, has been provided by several studies López-Barneo, 1991, 1992a,b;Pérez-García et al, 1992;López-López et al, 1993); however, no attempts have been made to establish the molecular identity of the different channels. Indeed, the minute size of the organ, together with its structural complexity, has delayed its characterization with conventional molecular biology techniques.…”
Section: Abstract: O 2 -Sensitive K ϩ Current; Viral Gene Transfer; mentioning
confidence: 99%
See 1 more Smart Citation
“…In rat type I cells, the current-voltage characteristics of maxiK channels suggest that they do not open until E m is more positive than Ϫ20 mV. Multiple studies have reported that specific maxiK blockers fail to activate isolated type I cells, which has supported the notion that these channels modulate cell activity and facilitate repolarization of the membrane (6,17,42). However, in thin slices of rat carotid body, Pardal and López-Barneo (37) demonstrated that the specific maxiK blocker iberiotoxin evokes catecholamine release from type I cells.…”
mentioning
confidence: 92%
“…Chemoreceptor cell culture and electrophysiological recordings Isolation and culture of chemoreceptor cells from adult rabbit CBs was done following protocols described previously (PerezGarcia, Obeso, Lopez-Lopez, Herreros & Gonzalez, 1992). In brief, CBs were incubated for 20 min at 37°C in 2 ml of nominally Ca2`-and Mg2+-free Tyrode solution (mM: NaCl, 140; KCl, 5; N-2-hydroxyethylpiperazine-N'-2-ethanesulphonic acid (Hepes), 10; glucose, 5; pH 7 2) containing trypsin (2 mg ml-', type II; Sigma, Alcobendas, Madrid, Spain) collagenase (2 mg ml-', type IV; Sigma), and deoxyribonuclease (DNase; 0 5 mg ml-', type II; Sigma).…”
mentioning
confidence: 99%